2000
DOI: 10.1177/096368970000900608
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1 Antisense Oligodeoxynucleotide Improves Islet Allograft Survival and Function

Abstract: Expression of intercellular adhesion molecule-1 (ICAM-1) and its ligand, leukocyte function antigen-1 (LFA-1), after pancreatic islet transplantation may affect both nonspecific and alloantigen-specific phases of graft destruction. We examined the effects of ICAM-1/LFA-1 blockade on the survival of islet allografts. Fresh C57BL/10 (H2h) pancreatic islets were transplanted under the renal subcapsular space (KC) or embolized into the liver after portal vein (PV) injection to C3H (H2k) mice. Recipients remained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…In the present study, a high systemic production of an immunoadhesin, using Ad-mediated in vivo transfer of the gene encoding sICAM-1/Ig, interfered with the LFA-1-ICAM-1 pathway and significantly prolonged islet allograft survival in mice. Monoclonal antibodies directed against ICAM-1 (Zeng et al, 1994;Katz et al, 2000), LFA-1 (Nishihara et al, 1997;Katz et al, 2000;Nicolls et al, 2000), or both (Grochowiecki et al, 2000;Katz et al, 2000) as well as ICAM-1 antisense oligonucleotides (Katz et al, 2000) have already been used in multiple animal models. According to these data, anti-LFA-1 MAb-specific tolerance has been reported using short-term administration of anti-LFA-1 MAb, confirming the critical role of the LFA-1-ICAM-1 pathway in allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, a high systemic production of an immunoadhesin, using Ad-mediated in vivo transfer of the gene encoding sICAM-1/Ig, interfered with the LFA-1-ICAM-1 pathway and significantly prolonged islet allograft survival in mice. Monoclonal antibodies directed against ICAM-1 (Zeng et al, 1994;Katz et al, 2000), LFA-1 (Nishihara et al, 1997;Katz et al, 2000;Nicolls et al, 2000), or both (Grochowiecki et al, 2000;Katz et al, 2000) as well as ICAM-1 antisense oligonucleotides (Katz et al, 2000) have already been used in multiple animal models. According to these data, anti-LFA-1 MAb-specific tolerance has been reported using short-term administration of anti-LFA-1 MAb, confirming the critical role of the LFA-1-ICAM-1 pathway in allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…The LFA-1-ICAM-1 interaction plays an essential role in the adhesion of leukocytes to endothelial cells, and is an important costimulatory signal in immunocompetent cells (Springer, 1994). Administration of anti-ICAM-1 and/or anti-LFA-1 monoclonal antibodies (MAbs) has been used in various allo-or xenograft rodent models such as heart (Isobe et al, 1992), islet (Gotoh et al, 1994;Zeng et al, 1994;Nishihara et al, 1997;Katz et al, 2000;Nicolls et al, 2000), small bowel (Sarnacki et al, 2000), pancreas (Kawabe et al, 1996), and liver transplantation (Harihara et al, 1996). Studies of humans confirmed that anti-ICAM-1 or anti-LFA-1 antibodies can significantly prolong kidney or bone marrow graft survival (Fischer et al, 1991;Haug et al, 1993;Hourmant et al, 1996).…”
Section: Introductionmentioning
confidence: 98%
“…Thus, Katz et al (2000) have explored the benefit of silencing ICAM-1 and its ligand, LFA-1, in mice pancreatic islet allotransplants by post-transplantation treatment of recipients with phosphorothioate ODNs. The authors observed that ICAM-1/LFA-1 blockade improved islet function and reduced inflammation compared with untreated controls (Katz et al, 2000).…”
Section: Antisense Oligonucleotides and Rna Interference For Gene mentioning
confidence: 99%
“…The potential of antisense technology is not confined to anti-viral therapy. Recently, antisense oligonucleotides have been used in diverse studies, examining allograft survival by targeting intracellular adhesion molecule-1 expression (Katz et al, 2000); inhibition of hepatoma growth by reducing vascular endothelial growth factor levels (Kang et al, 2000); reduction of FAS levels in the mouse liver to protect against acute liver failure ; and development of a tumor vaccine with molecules targeting TGF-b2 resulting in a reduction in tumor burden (Maggard et al, 2001).…”
Section: Ribozymes Antisense and Dna Ribonucleasesmentioning
confidence: 99%